"A Mirror and a Lamp": The Role of Power in the Rural Landscape Trajectory of the Ovens Region of Australia. Issue 8 (3rd August 2017) - Rawluk, Andrea; Curtis, Allan
ABSTRACT: Power relationships structure discourse and its influence on policy and rural land use planning, but little research has examined how this might be observed in the dynamics of rural landscape transition. In a qualitative case study of the Ovens catchment, Victoria, Australia, discursive power is observed through sites of tension between informant interpretations of past, present, and future landscapes and contemporary local decision making. Three main tensions and an observation emerged that suggest discourse and power can be observed through the transfer and support of social memory narratives. We conclude that the identification of tensions between stakeholder perceptions of the past, present, and future of their landscape; awareness of the influence of those interpretations on current decision making; and attention to social memory narratives can provide invaluable insights for those seeking to understand local relationships of power.